Bilateral Singapore fasciocutaneous flap after anterior vulvectomy and distal urethrectomy for localized recurrent vulvar carcinoma - Madison Crum; Caela Miller; Christopher Micallef; Richard Delaney; Erica Hope (Elsevier, 2024)
Introduction: Vulvar cancer has an overall low incidence, accounting for approximately 3-5% of all gynecological malignancies.Case: We present a case of locally recurrent Stage IIIA squamous cell carcinoma of the vulva in a 51-year-old healthy African American female. She was initially treated with primary chemoradiation with cisplatin sensitization and boost to primary tumor up to 70 Gray. Post-treatment biopsies revealed complete pathologic response. She later presented with local recurrence to the primary site of the clitoris and vulva, with no evidence of metastasis on imaging, with progressive disease despite treatment with immunotherapy. Methods: Biopsy-proven disease progression was present on the clitoris, entire left labia minora, and a portion of the right labia minora with no evidence of metastasis on imaging. Surgical resection for localized recurrence was recommended, and she underwent radical anterior vulvectomy, distal urethrectomy, and vulvar reconstruction with bilateral Singapore fasciocutaneous flap as part of a multidisciplinary team. Patient underwent several prophylactic hyperbaric oxygen treatments. There were no issues with postoperative wound healing. Conclusion: Treatment with radical excision often requires multidisciplinary teams for complex reconstructions to restore vulvar anatomy in the setting of prior radiation, especially for those patients desiring the ability to have penetrative intercourse in the future. There are few surgical videos that describe these types of vulvar excisions and subsequent reconstructions. This video provides a unique approach to vulvar reconstruction in a previously irradiated field.